Functionalization of Quinolines: Preparation of 2-Formyl-4-methoxy Quinolines - Sampathkumar, N.; Rajendran, S.P. (Asian Journal of Chemistry, 2016)
4-Methoxy-2-methyl quinolines (2) on oxidation by selenium dioxide under various conditions yield the hitherto unreported 2-formyl-4-methoxy quinolines (3), a useful synthon for the synthesis of higher nitrogen heterocycles.